2021
DOI: 10.1159/000512823
|View full text |Cite
|
Sign up to set email alerts
|

Doege-Potter Syndrome with a Benign Solitary Fibrous Tumor: A Case Report and Literature Review

Abstract: Doege-Potter syndrome is a rare paraneoplastic syndrome that is often diagnosed incidentally during the workup of hypoglycemia of unclear etiology. It is characterized by a non-islet cell tumor hypoglycemia secondary to excessive production of partially processed IGF-II hormone from a solitary fibrous tumor (SFT). Often these tumors are intrathoracic, benign, and asymptomatic. Occasionally they present as a paraneoplastic event; hypertrophic osteoarthropathy in Pierre-Marie-Bamberger syndrome and hypoglycemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 15 publications
3
30
0
Order By: Relevance
“…This hormone is responsible for glycemic control, and in Doege-Potter syndrome it is common for insulin levels to be decreased. As in previous studies, 5,6 our patient had low levels of basal insulin (0.04 U / I) and C-peptide (0.01 ng / dL).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This hormone is responsible for glycemic control, and in Doege-Potter syndrome it is common for insulin levels to be decreased. As in previous studies, 5,6 our patient had low levels of basal insulin (0.04 U / I) and C-peptide (0.01 ng / dL).…”
Section: Discussionsupporting
confidence: 81%
“…It has been described that the most frequent age of SFT is older adults. Several studies have reported SFT in patients aged 67 and 83 years, 5,9,11 although there are case series in patients aged 48 years, 12 52 years, 8 55 years, 6 and 58 years. 3 In this study, an elderly patient (74 years old) with Doege-Potter syndrome secondary to benign SFT was reported for the first time in Peru, which is different from previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…4 The SFT associated with Doege-Potter syndrome reported in this 74-year-old patient has demonstrated positivity for BCL2 +, focal CD34 +, and Focal CD99 +. Mohammed et al, 5 have reported a large number of lesions that are positive for CD34 + and CD99 +, as well as other case reports, have shown immunoreactivity of these cellular markers. 6,7 However, the authors emphasize that these immunohistochemical markers do not have high specificity and may be present in many soft tissue neoplasms.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have described complete resection as an effective treatment for this disease, as seen in some cases, including the one we reported in this article. 4,5,9 In addition, other surgical techniques with a favourable prognosis have been reported as successful. 3,13 With the discovery of the NAB2-STAT6 gene fusion as the characteristic molecular driver of SFT, it is possible that embolization therapy and radiation will be effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation